PENGELOLAAN RETRIBUSI TERMINAL DI KABUPATEN SAMBAS - Fajar Anggasuta E.42009004 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
This thesis is intended to find problems in the process management and problems of terminal charges in Sambas District. The title of this thesis was appointed by the problems that occur in the realization of the target receiving terminal in Sambas district levy in 2012 that did not hit the target as compared to previous years.This study used a qualitative approach in the hope that the data obtained more complete, thorough, credible, and more meaningful so that what is to be achieved in this study in accordance with the research objectives. This type of research is descriptive research that is intended to describe the actual state of the phenomenon that is happening in the community to determine the value of an independent variable, either a variable or more, regardless of the comparison or connection between one variable and the other variables on the phenomenon of research and social reality. In this study there is only one variable that researchers focus on the process of management of terminal charges in Sambas District, so the researchers expected to find the real problems in the management process for this terminal retribution.The conclusion of this study is that there are some problems in the implementation of fee collection terminal, such as a very minimal amount of personnel, lack of awareness of the public transport drivers of their obligation to pay the levy, and inadequate terminal facilities that led to the implementation of fee collection terminal can not be made maximally . So expect to all elements involved in the management of terminal charges to make the maximum contribution that those objectives can be achieved as expected. Keywords: Management, Terminal Charges, Coordination, Facilities.